The prognostic value of physiological and physical characteristics in youth soccer: A systematic review - Murr, D.; Raabe, J.; Höner, O. (European Journal of Sport Science, 2018)
Talent identification and selection in soccer is typically based on subjective evaluations of experienced coaches. Recently, there has been a trend to complement these subjective assessments with objective tests. However, there is currently no comprehensive overview of the prognostic relevance of objective measurements in youth soccer. Therefore, the primary purpose of the current study was to systematically review published empirical studies related to the prognostic relevance of physiological (e.g. endurance and speed) and physical characteristics (i.e. height and weight). Of 6876 initially identified studies, nine articles were included. In those studies, endurance (nine studies), change of direction (seven), height (seven), and weight (seven) received the most meaningful consideration within the literature. In regard to physiological predictors, between 16 and 29 effect sizes were tested for endurance, sprint, and change of direction, and about half of them were found to be significant with small to moderate effects (0.37 = Mdn(d) = 0.57). In addition, while only investigated in two studies all tested effect sizes for repeated sprint ability were found to be significant. Despite their frequent consideration in the literature, low numbers of significant effect sizes (= 26%) and magnitude (0.23 = Mdn(d) = 0.29) were found for the physical predictors height and weight. Overall, results appear to be dependent on the respective study design and, in particular, moderator variables (i.e. soccer development stage, performance level T1/T2, prognostic period, and sample size). Consequently, additional research seems warranted to more comprehensively investigate the predictive relevance of the individual characteristics using more homogeneous study designs.